2019
DOI: 10.31795/baunsobed.581180
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoints of Social Studies Teacher Candidates about Instructional Material Development and Usage

Abstract: Bu araştırmanın amacı, sosyal bilgiler öğretmen adaylarının sosyal bilgiler derslerinde öğretim materyali geliştirme ve kullanımı hakkındaki görüşlerini keşfetmektir. Araştırmada nitel araştırma yöntemlerinden olgubilim (fenomenoloji) deseni kullanılmıştır. Araştırmaya 16 sosyal bilgiler öğretmen adayı (9 kadın, 7 erkek) katılmıştır. Katılımcılar, amaçlı örnekleme yöntemiyle seçilmiştir. Veri toplamak için yarı-yapılandırılmış görüşme formu, yapılandırılmamış gözlem notları ve dokümanlar kullanılmıştır. Araştı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…Previous studies (Yenice, 2003;Vilkoniene, 2009;Güven & Sülün, 2012;Özkaya, 2013;Sarıkaya, 2015;Tezel & Aydost, 2016) have shown that teaching supported by visual materials and enriched technology environment increases academic achievement. In addition to concretizing the concepts, the materials can be used for fun learning, creative support thinking, use in measurement and evaluation, curiosity awakening, improving visual memory, learning by doing and motivation other contributions, such as enhancement (Dere, 2019).…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Yenice, 2003;Vilkoniene, 2009;Güven & Sülün, 2012;Özkaya, 2013;Sarıkaya, 2015;Tezel & Aydost, 2016) have shown that teaching supported by visual materials and enriched technology environment increases academic achievement. In addition to concretizing the concepts, the materials can be used for fun learning, creative support thinking, use in measurement and evaluation, curiosity awakening, improving visual memory, learning by doing and motivation other contributions, such as enhancement (Dere, 2019).…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 99%
“…Technological breakthroughs, which have an important place in the rapid development and changes in the world, inevitably affect the world of education and training. In particular, the rapid changes and inventions in information technologies in recent years have brought significant contributions to the field of education and training as well as the comfort and benefits they bring to all areas of life (Yuen et al, 2013;Pamuk et al, 2013;Somyürek, 2014;Karacaoğlu,2020;Dere & Demirci, 2021). Information and communication technologies have an important role to play in ensuring intercultural and interdisciplinary integration.…”
Section: Introductionmentioning
confidence: 99%
“…Daha da önceki çalışmaların sonuçlarına baktığımızda Kolb'a göre daha çok yerleştiren ve değiştiren öğrenme stiline sahip olunduğu yer almaktadır. Ayrıca öğrencilerin öğrenme stillerine sahip olma durumlarının cinsiyetlerine göre değişmediği de mevcut bulgular arasındadır (Özdemir ve Kesten, 2012;Bahar ve Sülün, 2011;Kaleli Yılmaz ve ark. 2010).…”
Section: Sonuç Tartışmaunclassified
“…Eğitimde verimin artması için öğrenci ve öğretmenlerin teknolojiyi etkin ve verimli olarak kullanması zaruri hale gelmiştir. Bu nedenle eğitimde toplumsal ve bireysel hedeflere ulaşmak için teknolojiden etkin bir şekilde yararlanması kaçınılmaz bir durumdur (Dereli, 2017).…”
Section: Introductionunclassified